2016
DOI: 10.4314/ahs.v16i2.5
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of trends and patterns of congenital heart disease in children in Nigeria from 1964-2015

Abstract: Background: Congenital heart diseases cause significant childhood morbidity and mortality. Several restricted studies have been conducted on the epidemiology in Nigeria. No truly nationwide data on patterns of congenital heart disease exists. Objectives: To determine the patterns of congenital heart disease in children in Nigeria and examine trends in the occurrence of individual defects across 5 decades. Method: We searched PubMed database, Google scholar, TRIP database, World Health Organisation libraries an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
19
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 25 publications
4
19
0
Order By: Relevance
“…In the Chinese study, prevalence of all types of VSD was 3.7/1,000 and tetralogy of Fallot was also the most common cyanotic congenital heart defect. A study in Nigeria reported similar findings [ 15 ]. In Brazil, a recent study reported a prevalence of congenital heart disease of 0.5 per 1000 live births across the country.…”
Section: Discussionsupporting
confidence: 70%
“…In the Chinese study, prevalence of all types of VSD was 3.7/1,000 and tetralogy of Fallot was also the most common cyanotic congenital heart defect. A study in Nigeria reported similar findings [ 15 ]. In Brazil, a recent study reported a prevalence of congenital heart disease of 0.5 per 1000 live births across the country.…”
Section: Discussionsupporting
confidence: 70%
“…The maximum score of the 8-item Morisky Medication Adherence Scale reported by 209 caregivers was 8, the minimum score was 2.5, with an overall mean score of 5.65 (standard deviation 1.36). Of the 209 respondents, 101 (48.3%) had a low compliance score (<6) and 108 (51.7%) respondents had a medium to high compliance score (6)(7)(8). Notably, only five respondents complete the 8-item Morisky Medication Adherence Scale with a maximum score of 8.…”
Section: Compliance With Aspirinmentioning
confidence: 99%
“…[4][5][6][7] The two most common types of CHD are ventricular septal defect and atrial septal defect, which accounts for 31.49 and 20.20% of CHD, respectively. 8,9 With the development of medical technology, medical devices, and surgical treatment of CHD, minimally invasive procedures are becoming more common in paediatric cardiology. Since the introduction of the Amplatser occlusion device at the end of the last century, which had a positive effect on the treatment of left-to-right shunt CHD, interventional therapy has gradually developed into the first choice of treatment for some forms of CHD.…”
mentioning
confidence: 99%
“…10 The spectrum of cardiac diseases seen among these children in our study is similar to what has been documented in literature, with CHD been the most prevalent cardiac disease and VSD the commonest type. 4,5,8,9,[11][12][13] A recent review of the trends and patterns of congenital heart disease in Nigeria over a five decades period also showed that acyanotic CHD is the most common form with VSD as the most prevalent. 13 Of the cyanotic CHD, TOF was the most common type encountered.…”
Section: Figmentioning
confidence: 99%